Pembangunan Daerah Dalam Era Reformasi - Leo Agustino (Jurnal Administrasi Publik, 2008)
After resignation of Soeharto in 1998, Indonesia political context especially in local level was change. The most significant change in current times is shifting paradigm from centralized government system to decentralized government system. But, this dramatically change is still problematic. Norms, values, and procedures were built by New Order regime still live in local government culture an attitude. Hence, in term of decentralization, local government must take a chance to change this culture. One solution was offer in this paper is implementing good governance.Keywords: regional development, good governance